Marka imajı ve tüketıcı algısı: uluslararası pazarda bir uygulama - Dario, Elnaz (My University, 2014)
Marka, Marka İmajı, Tüketici İmaj Algısı, Uluslararasi pazarlama ÖZET Bu tezde bir markanın imajı, tüketici marka imaj algısı dikkate alınarak incelenmiştir. Çalışmanın ana amacı; uluslararası pazarlamada tüketici marka imaj algısını etkileyen etmenlerin saptanması olarak belirlenmiştir. Bu çalışmada Avrupa’da saat sektöründen global bir marka olan ve başarılı bir uluslararası pazarlama stratejisi olan Swatch markasına yönelik tüketicilerin imaj algılarını etkileyen demografik faktörler Amerika birleşik devletleri ve Türkiye’de ölçülmüştür. Bu çalışmada kültürel ve siyasi yapı gibi tüketici marka imaj algısını etkileyen faktörler dışında, sadece demografik faktörler dikkate alınarak her iki farklı ülkede anket uygulaması yapılmıştır. Brand, Brand Image, Customer’s Perception of Brand Image, Global Marketing

This thesis is focused on customer’s perception of brand image. The main aim of this thesis is to analyze and understand effects of demographic profile on customer’s perception of an international brand in global market. This work would be a useful source and a contribution to future works and literature considering its ability to determine and assess parameters that affect customer’s perception of an international brand image in global market. Swatch as an international brand is selected for this study. Swatch has a perfect global marketing strategy for its target audience group around globe. Parameters affecting costumer’s perception of Swatch on global market is studied in two different countries, Turkey and United States. Influence of aforementioned parameters on these two countries being in different continents, having cultural and political structures differences is studied to understand Swatch’s brand image perception on global market.
Keywords: Endüstriyel yönetim; İhracat pazarlaması; Markalar; Markalaşma (Pazarlama); Markalı ürünler; Pazarlama; Üretim Yönetimi